Demographic Features of the Patients with Chronic Low Back Pain and Effectiveness of Back School - Murat Karkucak; İbrahim Tuncer; Mustafa Güler; Erhan Çapkın; Mehmet Tosun; Haşim Çakırbay (Archives of Rheumatology, 2006)
Objective: In this study, 44 patients with chronic low back pain, who have attended back school program, have been evaluated for effectiveness of this program, and their socioeconomic and low back pain features. Patients and Methods: In our series 72.7% of cases were females (47.7% were housewives), 40.9 had primary school education and 45.4% were between 35-44 years of age. Patients were evaluated before and 1 and 3 months after the back school training by the following parameters; Intensity of pain by Visual Analogue Scale (VAS), clinical assessment of lumbar region ((lumbar schoeber (cm), lumbar range of motion (ROM), straight leg raising test (SLRT)) , hand floor distance. Moreover, functional disability was assessed by the revised Oswestry Pain Questionnaire. Results: The results of pain intensity (VAS), lumbar ROM and functional disability after the back school were found to be significantly improved (p<0.05). Conclusion: It could be concluded that female sex and low educational level are important risk factors for back pain and back school is an effective adjunctive procedure in alleviating subjective and objective symptoms of patients with chronic low back pain. Also it may be concluded that back school be an alternative treatment procedure to other physical therapy modalities as it is a cost effective method. (Rheumatism 2006; 21: 87-90)